Theater and digital humanities - González Martínez, Javier J. (Talía. Revista de estudios teatrales, 2021)
Digital transformation and the success of technologies have radically modified our relationships, our connection with the world and our way of understanding ourselves. It is therefore not surprising that theater studies are affected by all these changes. But it is no less true that we run the risk of becoming clouded by what are means and ending up turning them into ends. Within Spanish theater studies, the digital humanities have found a well-prepared ground for sowing. And it is that the theater is an ideal object of study due to its transdisciplinarity. In addition, the theater allows the approach from very different perspectives and through various means so that the digital humanities can deploy a wide range of possibilities. Social media analysis can be applied to the internal relationships of characters and collaborative creation by writers. Georeferential tools like mapping make billboards and tours visible. Virtual recreation is rescuing lost spaces of representation. The databases allow the storage, connection and visualization of huge amounts of information related to the multiple agents (writers, directors, producers, printers, booksellers, actors), places (of representation, writing, sale), dates and formats of transmission. Stylometry can also bring many lights to a genre that blurs literary authorship in favor of representation. This monographic volume brings together articles focused on Spanish theater from the perspective of digital humanities. The objective of these preliminary pages is to show the value that each of the studies has in relation to the digital humanities. The articles can be grouped into three main fields: linguistic applications, databases and stylometry.
Keywords: Theater; Digital humanities; Database; Estylometry; linguistic applications; Databases